Novel noble-metal free S/Ni12P5/Cd0.5Zn0.5S composite with enhanced H2 evolution activity under visible light. (27th November 2020) - Guo, Minna; Guo, Xiaomin; Lin, Haili; Cao, Jing; Chen, Shifu
Abstract: Constructing composite photocatalyst is an efficient way to realize the application of photocatalysis owing to the fast separation of photocarriers. In this report, we constructed a novel ternary noble-metal free S/Ni12 P5 /Cd0.5 Zn0.5 S (S/Ni12 P5 /CZS) composite which displayed much higher activity than binary Ni12 P5 /CZS, S/CZS and especially CZS solid solution for H2 generation under visible light illumination (λ ≥ 420 nm). 15% S/Ni12 P5 /CZS showed the highest activity of H2 production (525.5 μmol h −1 ) among all the samples due to the optimal separating efficiency of photocarriers, and its apparent quantum efficiency is 4.37% at 420 nm. In the photocatalytic process, the photogenerated electrons of CZS solid solution quickly moved to elemental S through Ni12 P5 as solid electron transfer mediator, resulting in high separation efficiency of photocarriers and outstanding activity of H2 production over S/Ni12 P5 /CZS. Moreover, S/Ni12 P5 /CZS presented excellent stability after 10 runs recycling experiment. The significant finding of this paper provides new strategy to rationally design composite photocatalyst for efficiently splitting water to generate clean energy H2 . Highlights: Novel S/Ni12 P5 /Cd0.5 Zn0.5 S (S/Ni12 P5 /CZS) composite was firstly constructed. S/Ni12 P5 /CZS showed higher activity than Ni12 P5 /CZS and S/CZS for H2 generation. S/Ni12 P5 /CZS possessed the highest photo-charge separation efficiency. The photogenerated electrons of CZS transferred across Ni12 P5 to elemental S.